Ex Vivo Measurement of Human Blood T 1 at 5 T : Dependence on Hematocrit and Oxygenation - Shuwan Yu; Yuan Dong; Yuxiao Gu; Ne Yang; Lele Ma; Qingyu Xu; Ping Ma; Baoxin Zhou; Shuo Chen; Yonglin Chen; Dengrong Jiang; Xihai Zhao; et al. (Magnetic Resonance in Medicine, 2026)
ABSTRACT Purpose To determine human blood longitudinal relaxation time (T 1 ) ex vivo at 5 T using modified Look‐Locker inversion recovery (MOLLI), and to evaluate its dependence on hematocrit (Hct) and oxygenation ( Y ). Methods A MOLLI 5(3)3 protocol was simulated across T 1 values of 1000–3000 ms to optimize the sampling interval. Aqueous gadolinium phantoms were scanned using optimized MOLLI and multi‐inversion‐time recovery spin echo (IR‐SE) acquisitions to derive a calibration equation. Arm venous blood from 27 healthy volunteers (mean age: 23.7 ± 4.3 years; 10 males) was measured using optimized MOLLI, with three repetitions per sample. Hct and Y were measured by blood gas analysis, and their relationships with calibrated T 1 were evaluated. Results The minimum root mean square error (RMSE) was obtained at a MOLLI sampling interval of 2000 ms. In phantoms, MOLLI and IR‐SE T 1 showed a strong linear relationship: T 1,IR‐SE = 1.185 × T 1,MOLLI ‐93.746 ( R 2 = 0.998, p < 0.0001). In blood, MOLLI showed high repeatability, with an overall repeatability RMSE of 1.80 ms and a mean coefficient of variation of 0.10% ± 0.08%. Calibrated blood T 1 was 1933.6 ± 114.2 ms, range 1727.0–2128.0 ms. Blood 1/T 1 dependence on Hct and Y : 1/T 1 = 0.447–0.193 × Y + 0.447 × Hct + 0.150 ( Y × Hct) ( R 2 = 0.855, p < 0.0001), yielding an arterial blood T 1 of 1971 ms at Y = 0.98 and Hct = 0.42. Conclusion Optimized and phantom calibrated MOLLI enabled rapid measurement of human ex vivo blood T 1 at 5 T. Blood T 1 at 5 T was higher than commonly reported adult values at 3 T and varied with both Hct and Y .